How do Taxpayers Respond to Public Disclosure and Social Recognition Programs? Evidence from Pakistan - Joel Slemrod; Obeid Ur Rehman; Mazhar Waseem (Center for Economic Studies and ifo Institute (CESifo), 2020)
We examine two Pakistani programs to see if the public disclosure of tax information and social recognition of top taxpayers promote tax compliance. Pakistan began revealing income tax paid by every taxpayer in the country from 2012. Simultaneously, another program began recognizing and rewarding the top 100 tax paying corporations, partnerships, self-employed individuals, and wage-earners. We find that both programs induced strong compliance responses. The public disclosure caused on average a 9 log-points increase in the tax paid by individuals exposed to the program. The increase was even larger for the social recognition program, around 17 log-points. Our results suggest that such programs can be important policy levers to mobilize resources, especially in weak-enforcement-capacity economies.
Keywords: H24; H25; H26; 330; tax evasion; income tax; social norms